(untitled) (Medical Forum Monthly, 2024)
Objectives: To determine the diagnostic accuracy of risk of malignancy index (RMI) in the preoperative prediction of malignancy in ovarian masses by taking histopathological findings as gold standard. Study Design: Cross-sectional survey Place and Duration of Study: This study was conducted at Gynae Unit 111, Lady Willingdon Hospital Lahore and duration was one year from 1.1.2013 to 31.12.2013. Materials and Methods: 140 cases were recruited for the study. Blood drawn for serum Ca-125 level and sent to hospital laboratory and pelvic ultrasound was done. For each risk of malignancy index was calculated value of RMI > 200 was taken as positive. Results: Patients were having the mean age 55.8±7.6. Comparison of malignancy index vs. histopathology for prediction of malignancy in ovarian masses showed 64 malignant cases on histopathology and 69 on RMI. Sensitivity rate: 89.0%, specificity: 84.2%, diagnostic accuracy: 86.4%, PPV: 82.6% and NPV: 90.1%. Conclusion: The menopausal status, serum CA125 levels and ultrasound reports accumulated together can give us risk of malignancy index which can provide the odds of development of ovarian malignancies.